ANALISIS YURIDIS PERTIMBANGAN HAKIM IZIN POLIGAMI DAN HARTA BERSAMA (Studi Kasus Perkara Putusan Nomor 2/PDT.G/2025/PA.BBU) - Jaka Tri Junius; Sri Zanariyah; Januri Januri (Universitas Labuhanbatu, 2026)
Polygamy under Islamic law and Indonesian positive law is permissible only when strict legal requirements are fulfilled to safeguard the rights of wives, children, and jointly acquired marital property. Nevertheless, the judicial practice of granting polygamy permits continues to generate debate regarding the balance between procedural justice and substantive justice. This study aims to analyze the legal reasoning of judges in granting polygamy permits and its legal implications for the status of the first wife and jointly acquired property through an examination of Decision Number 2/Pdt.G/2025/PA.Bbu of the Blambangan Umpu Religious Court. The research employs a normative-empirical (socio-legal) approach using case and statutory approaches, supported by library research, judicial decision analysis, interviews, and observations. The findings reveal that the panel of judges based its decision on the first wife's health condition, the applicant's financial capability, and the wife's consent. However, the decision primarily emphasized compliance with formal legal requirements rather than critically assessing the voluntariness of the wife's consent and the protection of women's rights, thereby reflecting the predominance of procedural justice over substantive justice. Furthermore, the determination of jointly acquired property prior to the implementation of polygamy constitutes a preventive measure to protect the first wife's economic rights, although its effectiveness ultimately depends on the enforcement of the judgment and the husband's compliance with his legal obligations. The study recommends that Religious Courts adopt a more comprehensive assessment of the wife's consent and strengthen the protection of women's rights to ensure the realization of substantive justice in polygamy cases.Keywords: substantive justice; procedural justice; polygamy; protection of women's rights; judicial legal reasoning